Recanalization of acute carotid stent occlusion using Penumbra 4Max aspiration catheter: technical report and review of rescue strategies for acute carotid stent occlusion. (14th October 2013) - Munich, Stephan; Moftakhar, Roham; Lopes, Demetrius
Abstract : Carotid artery stenting (CAS) has become a widely used treatment for carotid artery stenosis, especially in high-risk patients. Acute in-stent and distal protection device occlusion are potentially catastrophic complications of this procedure. Previously described rescue strategies have included administration of antiplatelet agents (eg, abciximab) with/without thrombolytics and removal of the filter. Here we describe the successful resolution of in-stent occlusion by mechanical thrombolysis using the Penumbra 4Max aspiration catheter. Distal flow was subsequently restored with minimal residual stenosis. The patient did not suffer any consequent neurological deficits. The different strategies that could be used in this critical situation are reviewed.